Application of small angle X-ray scattering synchrotron technology for measuring ovine meat quality. (July 2016) - Hoban, J.M.; Hopkins, D.L.; Kirby, N.; Collins, D.; Dunshea, F.R.; Kerr, M.G.; Bailes, K.; Cottrell, J.J.; Holman, B.W.B.; Brown, W.; Ponnampalam, E.N.
Abstract: A small angle X-ray scattering (SAXS) synchrotron was used to evaluate 100 ovine m . longissimus lumborum, representing lamb (n = 50) and sheep (n = 50). The diffraction of X-rays gives information on muscle myofibril structure and fat content. The linear relationships between SAXS measures with measures such as, shear force, intramuscular fat content (IMF) and collagen content/solubility, were investigated. A relationship was found between the d-spacing of the actin/myosin fibril spacing (SAX1 and SAX2) and the cross sectional area of the rhombohedral unit cell (Cell area) and shear force after 1 and 5 day ageing. There was a positive relationship between IMF and a SAXS Fat area measure. There was a muscle site effect on SAX1, SAX2 and Cell area, with the cranial site having a larger distance between myofibrils. The potential of SAXS as a powerful research tool to determine not only the structural components of ovine tenderness, but also the fat content related to IMF is evident. Highlights: The spacing between actin and myosin filaments was measured using small angle X-ray scattering. This showed that such spacing was related to the shear force of ovine meat. SAXS was also used to determine the level of intramuscular fat (IMF). IMF determined chemically was strongly related to SAXS measures of fat level. SAXS data did change along the loin muscle suggesting muscle location needs to be considered.